Feasibility of a modified hybrid glubran-supported single-proglide technique for access closure during endovascular aneurysm repair - Xu, Chen; Xu, Guo-xiong; Chen, Lei; Zhang, Zhi-xuan; Jin, Yi-qi (Frontiers in Cardiovascular Medicine, 2024)
Objective This study aimed to evaluate the feasibility of a hybrid Glubran-supported single-Proglide technique for large bore femoral access closure during percutaneous access endovascular aneurysm repair (EVAR). Methods A retrospective cohort study was performed for all percutaneous EVARs at our center from January 2023 to June 2023. All patients received the hybrid Glubran-supported single-Proglide technique involving a mixture of surgical glue and Lipiodol injection after single suture placement for femoral access closure. Technical success was defined as achieving complete hemostasis without a bailout strategy. Vascular complications and bleeding were defined by Valve Academic Research Consortium-3 (VARC-3) criteria. Vascular access changes and 30-day mortality were recorded. Results The technique success rate for the entire study population was 100% (55 femoral access in 37 patients; median age: 72; 78% males). The mean sheath size was 20.4 ± 2.3F. The mean manual compression time was 3.5 ± 1.4 min, the mean hemostasis time was 9.0 ± 2.5 min, and the mean procedural time was 103.9 ± 34.7 min. One patient (1.6%) developed an access site infection and recovered conservatively. No VARC-3 vascular complications and access changes were observed. No 30-day mortality happened. Conclusions The hybrid Glubran-supported single-Proglide technique is feasible for large bore access closure during EVAR and may be a viable alternative; however, larger prospective studies are required to confirm its efficacy.